Indonesia Passenger’s Right Compensation for Transport Accidents: Is It Fulfilling a Sense of Justice? - Nurbaiti, Siti (Hasanuddin Law Review, 2024)
The mode of transportation—whether on land, at sea, or in the air—plays a crucial role in passenger mobility across various countries. Between passengers and carriers, binding contracts establish their legal relationship. However, a persistent issue remains: to what extent should carriers be held liable in cases of loss, injury, or death of passengers, and what are their obligations regarding compensation? The key question revolves around the scope of the carrier's responsibility to compensate passengers. As such, regulations governing carrier liability and compensation have become a critical focus in international legal studies, including in Indonesia, with comparisons drawn to several Southeast Asian countries. This research employs normative legal methodology with a conceptual framework. It is analyzed descriptively using a qualitative approach and concludes through deductive reasoning. The findings suggest that passenger compensation in several Southeast Asian countries does not fully satisfy the sense of justice. While there are regulations addressing compensation, they are often insufficiently stringent. In cases where accidents lead to legal action, the compensation amount is typically determined by the presiding judges on a case-by-case basis.